Novel Synthetic Opioids (NSO) Use in Opioid Dependents Entering Detoxification Treatment - Specka, Michael; Kuhlmann, Thomas; Bonnet, Udo; Sawazki, Jürgen; Schaaf, Luzia; Kühnhold, Stefan; Steinert, Renate; Grigoleit, Torsten; Eich, Helmut; Zeiske, Benita; Niedersteberg, Antje; Steiner, Katharina; et al. (Frontiers in Psychiatry, 2022)
Introduction: Over the last decade, the use of New/Novel Synthetic Opioids (NSO) has emerged as an increasing problem, and especially so in the USA. However, only little is known about the prevalence and history of NSO use in European heroin dependents. Method: A cross-sectional multicenter study carried out, with the means of both standardized interviews and urine toxicology enhanced screening, in a sample of opioid addicted patients referred for an in-patient detoxification treatment. Results: Sample size included here n=256 patients; prior to admission, 63.7% were prescribed with an opioid maintenance treatment. Lifetime use of heroin and opioid analgesics were respectively reported by 99.2% and 30.4%. Lifetime NSO/fentanyl use was reported by 8.7% (n=22); a regular use was reported by 1.6% (n=4), and ingestion over the 30 days prior to admission by 0.8% (n=2). Most typically, patients had started with a regular consumption of heroin, followed by maintenance opioids; opioid analgesics; and by NSO. Self-reported data were corroborated by the toxicology screenings carried out; no evidence was here identified for the presence of heroin being contaminated by fentanyl/derivatives. Discussion: NSO, or opioid analgesics, may not play a relevant role in the development and the course of opioid/opioid use disorders in German patients referred for an inpatient detoxification treatment.